Distribution of plant species with potential therapeutic effect in area of the Universiti Teknologi Mara (UiTM), Kuala Pilah Campus, Negeri Sembilan, Malaysia / Rosli Noormi ... [et al.] - Noormi, Rosli; Shamsuddin, Raba’atun Adawiyah; Abdullah, Anis Raihana; Yahaya, Hidayah; Mohd Zulkamal, Liana; Rosly, Muhammad Amar; Azmi, Nor Shamyza Azrin; Mohamad, Nur Aisyah; Sahabudin, Nur Syamimi Liyana; Raffin, Nur Yasmin; Rosali, Nurul Hidayah; Elias, Nurul Nasuha; et al. (Universiti Teknologi MARA, Negeri Sembilan, 2020)
Knowledge of species richness and distribution is decisive for the composition of conservation areas. Plants typically contain many bioactive compounds are used for medicinal purposes for several disease treatment. This study aimed to identify the plant species distribution in area of UiTM Kuala Pilah, providing research scientific data and to contribute to knowledge of the use of the plants as therapeutic resources. Three quadrat frames (1x1 m), which was labeled as Set 1, 2 and 3 was developed, in each set consists of 4 plots (A, B, C and D). Characteristics of plant species were recorded, identified and classified into their respective groups. Our findings show that the most representative classes were Magnoliopsida with the total value of 71.43%, followed by Liliopsida (17.86%) and Lecanoromycetes (10.71%). A total of 28 plant species belonging to 18 families were identified in all sets with the largest family of Rubiaceae. The most distribution species are Desmodium triflorum, Dactyloctenium aegyptium, Flavoparmelia caperata, Xanthoria elegans and Phlyctis argena. Most of the plant possesses their potential to treat skin diseases, fever, ulcers and diabetes as well as digestive problems with their antimicrobial, anti-inflammatory and antioxidant properties. This study suggests that study site and plant species can be delineated as an important area to preserve these therapeutic resources. Finally, this study could also be useful for preliminary screening of potential therapeutic plant found in the study area and useful for the researchers in the pursuit of novel drug discovery.